2002
DOI: 10.1056/nejmoa010877
|View full text |Cite|
|
Sign up to set email alerts
|

Daily Hemodialysis and the Outcome of Acute Renal Failure

Abstract: The high mortality rate among critically ill patients with acute renal failure who require renal-replacement therapy is related to both coexisting conditions and uremic damage to other organ systems. Intensive hemodialysis reduces mortality without increasing hemodynamically induced morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
350
7
30

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 750 publications
(406 citation statements)
references
References 14 publications
14
350
7
30
Order By: Relevance
“…Our study demonstrated a shorter duration of ICU stay and a trend for a shorter duration of RRT with the lower-volume protocol, in contrast to previous reports, where high-volume therapy was associated with a shorter duration of RRT, ICU stay and/or ventilatory support [1,4]. In our study, this difference is most likely to reflect differences between the two cohorts rather than an effect of the RRT protocol switch; the low-volume cohort had a higher incidence of CKD at baseline, and fewer patients required ventilatory support.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study demonstrated a shorter duration of ICU stay and a trend for a shorter duration of RRT with the lower-volume protocol, in contrast to previous reports, where high-volume therapy was associated with a shorter duration of RRT, ICU stay and/or ventilatory support [1,4]. In our study, this difference is most likely to reflect differences between the two cohorts rather than an effect of the RRT protocol switch; the low-volume cohort had a higher incidence of CKD at baseline, and fewer patients required ventilatory support.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, leptospirosis is a near-perfect human model of sepsis. Schiffl et al (9) reported that daily intermittent hemodialysis is superior to conventional (alternate-day) hemodialysis in critically ill patients with AKI and concomitant acute tubular necrosis. The authors found that daily hemodialysis was associated with better control of blood urea nitrogen and creatinine, as well as with higher survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…Survival did not significantly differ between groups 2 and 3 (P Ͼ 0.2). Moreover, Schiffl and colleagues (112) recently reported that among 160 consecutive patients alternately assigned to daily or alternate-day hemodialysis with a biocompatible membrane (high-flux polysulfone or AN 69), mortality was reduced from 46% to 28% with daily dialysis (P ϭ 0.01). The weekly delivered dose of dialysis was greater for the daily group than for the alternate-day group.…”
Section: Initiation and Dosementioning
confidence: 99%